Anesthetic Related Advances with Cyclodextrins - Mark Welliver; John P. McDonough (The Scientific World Journal)
Cyclodextrins encapsulate and electrostatically bind to lipophilic molecules. The exterior of cyclodextrins are water-soluble and maintain aqueous solubility despite encapsulation of non-aqueous soluble molecules. This unique ability to encapsulate lipophilic molecules and maintain water solubility confers numerous pharmacologic advantages for both drug delivery and removal. Cyclodextrins, a component part of supramolecular chemistry, may be in its infancy of anesthetic application but recent advances have been described as novel and revolutionary. A review of current research coupled with an understanding of cyclodextrin properties is necessary to fully appreciate the current uses and future potentials of these unique molecules.